2015
DOI: 10.5812/archneurosci.23315
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Tissue Plasminogen Activator Administration in Patients With Cerebrovascular Accident; A Case Series

Abstract: Background: Cerebrovascular accident (CVA), as a debilitating neurological impairment, is one of the most common causes of death in adults. It is observed that CVA is less well-documented in the developing countries compared to the developed ones and most of the available data are based on case series. Objectives: The current study aimed to evaluate the effectiveness, feasibility, outcome, and safety of intravenous recombinant tissue plasminogen activator (IV rt-PA) administration in patients with acute ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In these cases, the blocked vessel can be opened by thrombolytic therapy or thrombectomy within a few hours of the onset of symptoms (2,3). However, a few patients receive such treatments, which is mainly due to the delay in arriving at a hospital (4,5). Emergency medical service (EMS) can play a vital role in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the blocked vessel can be opened by thrombolytic therapy or thrombectomy within a few hours of the onset of symptoms (2,3). However, a few patients receive such treatments, which is mainly due to the delay in arriving at a hospital (4,5). Emergency medical service (EMS) can play a vital role in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence of stroke has been estimated to be about 15 million cases that onethird die and one-third suffer from a permanent disability. In total, more than 80% of all stroke-induced deaths in the world occur in developing countries (1)(2)(3)(4)(5)(6)(7)(8). Previous studies have shown that the risk of stroke is doubled after the age of 55.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the efficiency of recombinant tissue plasminogen activator (rt-PA) and findings have revealed acceptable outcomes concerning the prescription of this drug between 3 and 4.5 hours after the onset of the symptoms (9). However, the use of this drug requires the proper awareness of the society in identifying stroke symptoms, early referral of patients, the quality of life, speed of laboratory and imaging services, timely visits by neurologist, early treatment and observing certain clinical principles (10,11). Due to several preventive factors in the prescription of the drug, only a small percentage of patients could receive the rt-PA (12).…”
Section: Introductionmentioning
confidence: 99%